A randomized, sham-controlled clinical trial to evaluate the NET Device™ for reducing withdrawal symptom severity during opioid discontinuation - Greenwald, Mark K.; Arfken, Cynthia L.; Winston, Joe R. (Frontiers in Psychiatry, 2025)
BackgroundNeuromodulation is a promising approach for opioid discontinuation, as not all patients with opioid use disorder (OUD) seek pharmacotherapy. The NET Device is a non-invasive, battery-powered, portable, device that provides bilateral, transcranial, transcutaneous, alternating current stimulation (tACS) for patients experiencing opioid withdrawal. This clinical trial prospectively evaluated whether NET Device utilization is effective for persons with OUD undergoing opioid discontinuation without medications for OUD (MOUD).MethodsThis randomized, sham-controlled trial was conducted at a single residential treatment center. Persons with OUD undergoing opioid discontinuation were assigned to active or sham device treatment. Clinical Opiate Withdrawal Scale (COWS) total scores were measured prior to and during device use. We tested whether active stimulation would produce a clinically meaningful (≥15%) decrease in COWS score from baseline to 1-hr post-stimulation, compared to sham.Results108 participants (55 sham, 53 active; 59.3% male, 89.8% white; 71.3% fentanyl-positive) form the intent-to-treat dataset. Mean ( ± 1 SD) COWS score in the active device group decreased from baseline (18.1 + 4.4) to 1-hr (7.0 + 4.1); this 61.3% decrease (d=2.14) exceeded the pre-specified 15% criterion. COWS scores decreased more for active (-11.1 ± 5.2) than sham (-8.8 ± 6.3), p<.05, d=-.41. A higher proportion of participants in active vs. sham showed ≥15% reduction in COWS (98.1% vs. 83.6%), p=.016. Device utilization was longer for active than sham, 43.9 + 46.2 vs. 30.0 + 39.2 hours, p=.008, and fewer participants requested MOUD (26% vs. 49%, p<0.02).ConclusionThe NET Device is effective, safe and well-tolerated for reducing opioid withdrawal symptoms. This device received FDA market clearance in May 2024.Clinical trial registrationClinicalTrials.gov, identifier NCT04916600.